Effects of essential oils on calf growth, ruminal fermentation, and antioxidative status: a meta-analysis - Li, Wei; Wang, Fang; Han, Yongsheng; Sun, Fang; Liu, Chunhai; Zhu, Yuanfang; Zhong, Peng (Frontiers in Veterinary Science, 2025)
IntroductionEssential oils (EO) have gained significant attention in the calves industry due to their antimicrobial properties. This meta-analysis aimed to evaluate the efficacy of EO on calves to provide better guidance for cattle feed.MethodsWe conducted a comprehensive search of relevant studies published from inception to February 6, 2022, using PubMed, CENTRAL,Web of Science, and EMBASE. The quality of included studies was assessed using the CAMARADES checklist. Effect sizes were calculated using weighted mean differences (WMD) for continuous variables and summary risk ratios (RR) for binary variables. Subgroup and sensitivity analyses were also performed.ResultsThis systematic review and meta-analysis included 10 animal studies with 226 calves. The average quality score was 5.8 (range: 5–7). EO improved milk production (WMD = 0.30; 95% CI 0.13 to 0.47; I2 = 0%, p = 0.985) and beta-hydroxybutyric acid levels (WMD = 0.01; 95% CI 0.04 to 0.16; I2 = 0%, p = 0.472). However, EO did not significantly improve rumen fermentation characteristics or overall performance index.DiscussionWhile EO may have beneficial effects on specific outcomes like milk production and beta-hydroxybutyric acid levels,its impact on rumen fermentation and overall performance remains inconclusive. Future large-scale randomized controlled trials (RCTs) are needed to better assess the effects of EO on ruminal fermentation efficiency, anti-oxidative status, and overall performance.